Improving Language Learning Strategies and Performance of Pre-Service Language Teachers Through a CALLA-TBLT Model - Maria Eugenia Guapacha Chamorro; Luis Humberto Benavidez Paz (Universidad Nacional de Colombia, 2017)
This paper reports an action-research study on language learning strategies in tertiary education at a Colombian university. The study aimed at improving the English language performance and language learning strategies use of 33 first-year pre-service language teachers by combining elements from two models: the cognitive academic language learning approach and task-based language teaching. Data were gathered through surveys, a focus group, students' and teachers' journals, language tests, and documentary analysis. Results evidenced that the students improved in speaking, writing, grammar, vocabulary and in their language learning strategies repertoire. As a conclusion, explicit strategy instruction in the proposed model resulted in a proper combination to improve learners' language learning strategies and performance.